A Comparative Study between Implicit and Crank-Nicolson Finite Difference Method for Option Pricing - Debnath, Tanmoy Kumar; Hossain, ABM Shahadat (GANIT: Journal of Bangladesh Mathematical Society, 2020)
In this paper, we have applied the finite difference methods (FDMs) for the valuation of European put option (EPO). We have mainly focused the application of Implicit finite difference method (IFDM) and Crank-Nicolson finite difference method (CNFDM) for option pricing. Both these techniques are used to discretized Black-Scholes (BS) partial differential equation (PDE). We have also compared the convergence of the IFDM and CNFDM to the analytic BS price of the option. This turns out a conclusion that both these techniques are fairly fruitful and excellent for option pricing. GANIT J. Bangladesh Math. Soc.Vol. 40 (2020) 13-27